MgNb2O6:Dy3+ nanophosphor: A facile preparation, down conversion photoluminescence and UV driven photocatalytic properties. Issue 7 (1st April 2021) - Basavaraju, N.; Prashantha, S.C.; Nagabhushana, H.; Pratapkumar, C.; Ravikumar, C.R.; Kumar, M.R. Anil; Surendra, B.S.; Shekhar, T.R. Shashi; Premkumar, H.B.; Nagaswarupa, H.P.
Abstract: Series of (1–9 mol %) dysprosium (Dy 3+ ) ions doped MgNb2 O6 (MNO) nanophosphors were synthesized by chemical combustion process and their photo luminescent and photocatalytic behaviours were examined. Powder X-ray diffraction (PXRD) reveals the columbite structure and crystal structure parameters were calculated. The average crystallite size was found to be in the range of 20–30 nm as calculated by Scherrer's method. The photoluminescence (PL) of MgNb2 O6 :Dy 3+ (λexc -393 nm) reflects white emission for the prepared samples as confirmed by CIE and CCT. The photocatalytic activities of these nanophosphors were probed for the decolorization of acid red 88 (AR-88) under UV light irradiation. The photocatalyst with MgNb2 O6 :Dy 3+ (5 mol %) showed enhanced activity of 97%, attributed to effective separation of charge carriers. All the above experimental results confirm that, the optimized phosphor is quite useful for WLEDs, solid-state lighting applications and as a photocatalyst.